2022
DOI: 10.1038/s43016-022-00460-8
|View full text |Cite
|
Sign up to set email alerts
|

Policy framing, design and feedback can increase public support for costly food waste regulation

Abstract: About one-third of all food produced for human consumption worldwide is wasted, particularly in highincome countries. Reducing this waste is key to decreasing negative environmental impacts from the food sector and increasing food security in developing countries. Yet, achieving food waste reduction is challenging. It is widely presumed that efforts at stricter food waste regulation may increase food prices, and hence consumer and citizen opposition could render such ambitious regulation politically unfeasible… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Global food production is estimated to be 4 Gton/year, indicating that for each kg of food, 4.7 kg of CO 2 is generated and released into the environment. As mentioned in the introduction, approximately one-third of the food produced globally becomes wasted or lost, and it has recently been reported that this food loss accounts for 8–10% of total GHG emissions, equating to ∼4–5 Gton/year of CO 2 emissions . By taking the protein-rich byproducts discussed in this paper into account, in which the average protein content is approximately 32%, we find that for each kg of protein wasted, 14.6 kg of CO 2 is emitted in the environment.…”
Section: Outlook and Conclusionmentioning
confidence: 54%
See 2 more Smart Citations
“…Global food production is estimated to be 4 Gton/year, indicating that for each kg of food, 4.7 kg of CO 2 is generated and released into the environment. As mentioned in the introduction, approximately one-third of the food produced globally becomes wasted or lost, and it has recently been reported that this food loss accounts for 8–10% of total GHG emissions, equating to ∼4–5 Gton/year of CO 2 emissions . By taking the protein-rich byproducts discussed in this paper into account, in which the average protein content is approximately 32%, we find that for each kg of protein wasted, 14.6 kg of CO 2 is emitted in the environment.…”
Section: Outlook and Conclusionmentioning
confidence: 54%
“…As mentioned in the introduction, approximately one-third of the food produced globally becomes wasted or lost, and it has recently been reported that this food loss accounts for 8−10% of total GHG emissions, equating to ∼4−5 Gton/year of CO 2 emissions. 3 By taking the protein-rich byproducts discussed in this paper into account, in which the average protein content is approximately 32%, we find that for each kg of protein wasted, 14.6 kg of CO 2 is emitted in the environment. This review, however, focuses on protein-rich byproducts; we expect the average protein content in food waste to be lower than 32%, further increasing the predicted emissions of CO 2 for each kg of wasted protein to be well beyond 15 kg.…”
Section: Outlook and Conclusionmentioning
confidence: 91%
See 1 more Smart Citation
“…National Bureau of Statistics, the price index for livestock meat has been higher than the prices of other food categories from 2016-2020, limiting the number of purchases made by consumers and reducing waste by due to consumers' economic loss avoidance 23 , making the amount of waste correspondingly lower.…”
Section: Weighing Of Plate Leftoversmentioning
confidence: 99%
“…Food waste mitigation is a global problem, and many countries in the world have taken certain measures for food waste in terms of laws, systems, and policies. Policies play an important role in reducing food waste (Fesenfeld et al, 2022 ). Reducing food waste would contribute to addressing interconnected sustainability challenges, such as climate change, food security, and natural resource shortages.…”
Section: Introductionmentioning
confidence: 99%